2021
DOI: 10.48550/arxiv.2101.01100
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wasserstein barycenters are NP-hard to compute

Jason M. Altschuler,
Enric Boix-Adsera

Abstract: The problem of computing Wasserstein barycenters (a.k.a. Optimal Transport barycenters) has attracted considerable recent attention due to many applications in data science. While there exist polynomial-time algorithms in any fixed dimension, all known runtimes suffer exponentially in the dimension. It is an open question whether this exponential dependence is improvable to a polynomial dependence. This paper proves that unless P = NP, the answer is no. This uncovers a "curse of dimensionality" for Wasserstein… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 19 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…7 that the larger the batch, the more concentrated the trajectories of mn,s become. Additionally, Table 3 summarizes the means of the distance W 2 2 to the true model m 0 , using the sequences after t = 100 against the empirical estimator using all the simulations with k ≥ 100. Finally, Table 4 shows the standard deviation of the distance W 2 2 to the true model m 0 , which can be seen to decrease as the batch size grows.…”
Section: Distance Between the Empirical Barycenter And The Bayesian M...mentioning
confidence: 99%
See 1 more Smart Citation
“…7 that the larger the batch, the more concentrated the trajectories of mn,s become. Additionally, Table 3 summarizes the means of the distance W 2 2 to the true model m 0 , using the sequences after t = 100 against the empirical estimator using all the simulations with k ≥ 100. Finally, Table 4 shows the standard deviation of the distance W 2 2 to the true model m 0 , which can be seen to decrease as the batch size grows.…”
Section: Distance Between the Empirical Barycenter And The Bayesian M...mentioning
confidence: 99%
“…We refer the reader to the overview [38] for statistical applications, to the works [12,15,16,41] for applications in machine learning, and to [3,4,10,33] for a presentation of recent developments and further references. As a cautionary tale, we mention that the problem of computing Wasserstein barycenters is known to be NP-hard, see [2]. To cope with this, fast methods aiming at learning and generating approximate Wasserstein barycenters on the basis of neural networks techniques, have also been proposed, see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This eliminates the exponential dimension dependence of state-of-the-art convergence rates [Che+20], which aligns with the empirical performance of this algorithm (see Figure 1). It also stands in sharp contrast to the setting of discrete distributions in which there are computational complexity barriers to achieving even polynomial dimension dependence [AB21b].…”
Section: Contributionsmentioning
confidence: 99%
“…The second is that generically, these problems are computationally hard in high dimensions. For instance, Wasserstein barycenters and geometric medians of discrete distributions are NP-hard to compute (even approximately) in high dimension [AB21b].…”
Section: Introductionmentioning
confidence: 99%
“…However, this approach does not scale well with the dimension as noted by Altschuler and Boix-Adserà (2021). Indeed, they showed that computing the infimum of ν → λ i W 2 2 (µ i , ν) when the µ i are discrete measures is a NP-hard problem in the dimension, even when only approximate solutions are acceptable.…”
Section: Introductionmentioning
confidence: 99%